A-STATE-OF-ART REVIEW ON ADDITIVES FUNCTION ON POLYMERIC MEMBRANE PERFORMANCE FOR WASTEWATER TREATMENT - Sri Martini; Dian Kharismadewi; Erna Yuliwati (Jurnal Dinamika Penelitian Industri, 2021)
In this article, the recent development of polymeric membrane fabrication using additive for wastewater treatment is presented. The application of this substance has been recognized reliable to increase membrane performance against fouling phenomenon, especially for purifying industrial wastewaters that mostly have high loading of hazardous pollutants. The effects of modification techniques through additives addition on membrane casting solution are considerably included. This paper also discusses membrane fouling mechanism and other existing technologies available for treating contaminated water. Despite the existence of review paper discussing membrane fouling mitigation on literature, there is still the need of comprehensive review related to the novel technology regarding additive blending on membrane, especially on polymer-based membrane for water pollution control. Eventually, clear conclusion can be drawn that the suitability of additive substances and its composition as well as suitable operating conditions have great leverage on polymeric membrane performance regarding its anti-fouling and hydrophilic level.